Daphnoretin Induces Cell Cycle Arrest and Apoptosis in Human Osteosarcoma (HOS) Cells - Gu, Shoubin; He, Jinhai (Molecules (Basel, Switzerland), 2012)
In this study antiproliferation, cell cycle arrest and apoptosis induced by daphnoretin in human osteosarcoma (HOS) cells were investigated. Antiproliferative activity was measured with the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The IC50 value of daphnoretin was 3.89 μM after 72 h treatment. Induction of apoptosis was evidenced by apoptotic body appearance and Annexin V-FITC/PI apoptosis detection kit. Flow cytometric analysis indicated daphnoretin arrested the cell cycle in the G2/M phase. Western-blot assay showed that the G2/M phase arrest was accompanied by down-regulation of cdc2, cyclin A and cyclin B1. Moreover, daphnoretin inhibited Bcl-2 expression and induced Bax expression to desintegrate the outer mitochondrial membrane and causing cytochrome c release. Mitochondrial cytochrome c release was associated with the activation of caspase-9 and caspase-3 cascade. Our results demonstrated that daphnoretin caused death of HOS cells by blocking cells successively in G2/M phases and activating the caspase-3 pathway.